Sublingual Film Formulation of Tempuyung Leaf Extract (Sonchus Arvensis L.) as Anthyperuricemic Agent - Subagja, Seina Lathifa; Nurdianti, Lusi; Agustiani, Dika Tri; Jayanty, Rizka Sri; Khaelani, Eka; Dwi Lestari, Oktaviana (Universitas Tidar, 2025)
Tempuyung leaves (Sonchus arvensis L.) are known to contain flavonoid compounds with potential antihyperuricemic activity. This study aimed to prepare Sonchus arvensis leaf extract and formulate it into a sublingual thin film dosage form to develop a therapeutic formulation for the treatment of hyperuricemia. The study employed a Completely Randomized Design using 24 rats (Rattus norvegicus), divided into six groups: positive control (Allopurinol), negative control, blank, and three treatment groups receiving Sonchus arvensis extract at doses of 50 mg/70 kg BW, 100 mg/70 kg BW, and 200 mg/70 kg BW. The sublingual film formulation was prepared using the solvent casting method. Data were analyzed using ANOVA and LSD tests. The results indicated that Formula 3, with a dose of 200 mg, produced the most significant reduction in uric acid levels. Standardization parameters of the extract, including moisture content, ash content, water-soluble extract, ethanolsoluble extract, and loss on drying, complied with the applicable standards. Evaluation of the sublingual film demonstrated that the formulation met the required characteristics and quality standards for sublingual films. In conclusion, the sublingual film of Sonchus arvensis leaf extract shows potential as an effective antihyperuricemic agent. Keywords: Tempuyung Leaves, Antihyperuricemia, Thin Film